2014
DOI: 10.1002/ppul.23032
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost for children with pulmonary hypertension after surgery to correct congenital heart disease

Abstract: Congenital heart disease (CHD) can cause pulmonary hypertension (PH) in children, and surgery to correct CHD may be complicated by postoperative pulmonary hypertensive crises (PHC). Clinical data regarding the use of inhaled iloprost to treat children with PH are scarce. Our aim was to determine the efficacy and safety of iloprost in children with PH following surgery to correct CHD. This was a randomized, placebo-controlled study of 22 children (median age 7 months) undergoing surgery to achieve biventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…Besides, no deaths occurred in the PGI 2 studies during follow-up, which also demonstrates the safety of PGI 2 . Compared with the previous studies in adults, adverse events in the present study for sildenafil were headache (34% in adult vs. 13% in pediatric patients), gastrointestinal upset (26% in adult vs. 11% in pediatric patients), respiratory symptoms (11% in adult vs. 12% in pediatric patients), and epistaxis (6% in adult vs. 3% in pediatric patients) (Peiravian et al, 2007;Cornelisse et al, 2012;Barnes et al, 2019); the adverse events for bosentan were headache (21% in adult vs. 0% in pediatric patients), respiratory symptoms (8% in adult vs. 9% in pediatric patients), abnormal hepatic function (9% in adult vs. 0% in pediatric patients), red blood cell transfusion (0% in adult vs. 31% in pediatric patients), and anemia (0% in adult vs. 23% in pediatric patients) (Rubin et al, 2002;Gibbs and Ismail, 2012;Steinhorn et al, 2016); and the adverse events for beraprost sodium and iloprost treatment were headache (53% in adult vs. 0% in pediatric patients), upper respiratory tract events (34% in adult vs. 0% in pediatric patients), nausea or vomiting (43% in adult vs. 0% in pediatric patients), PH crisis (6% in adult vs. 7% in pediatric patients), and thrombocytopenia (0% in adult vs. 27% in pediatric patients) (Xu et al, 2015;Onan et al, 2016;Pulido et al, 2019). All pediatric PH patients well tolerated the pulmonary vasodilators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, no deaths occurred in the PGI 2 studies during follow-up, which also demonstrates the safety of PGI 2 . Compared with the previous studies in adults, adverse events in the present study for sildenafil were headache (34% in adult vs. 13% in pediatric patients), gastrointestinal upset (26% in adult vs. 11% in pediatric patients), respiratory symptoms (11% in adult vs. 12% in pediatric patients), and epistaxis (6% in adult vs. 3% in pediatric patients) (Peiravian et al, 2007;Cornelisse et al, 2012;Barnes et al, 2019); the adverse events for bosentan were headache (21% in adult vs. 0% in pediatric patients), respiratory symptoms (8% in adult vs. 9% in pediatric patients), abnormal hepatic function (9% in adult vs. 0% in pediatric patients), red blood cell transfusion (0% in adult vs. 31% in pediatric patients), and anemia (0% in adult vs. 23% in pediatric patients) (Rubin et al, 2002;Gibbs and Ismail, 2012;Steinhorn et al, 2016); and the adverse events for beraprost sodium and iloprost treatment were headache (53% in adult vs. 0% in pediatric patients), upper respiratory tract events (34% in adult vs. 0% in pediatric patients), nausea or vomiting (43% in adult vs. 0% in pediatric patients), PH crisis (6% in adult vs. 7% in pediatric patients), and thrombocytopenia (0% in adult vs. 27% in pediatric patients) (Xu et al, 2015;Onan et al, 2016;Pulido et al, 2019). All pediatric PH patients well tolerated the pulmonary vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…Among the fifteen included studies, three had an ERA group and control group (Gibbs and Ismail, 2012;Pan and Kong, 2016;Steinhorn et al, 2016), nine had PDE5i and control groups (Juni et al, 2006;Wessel et al, 2006;Peiravian et al, 2007;Kolaee et al, 2009;Vargas-Origel et al, 2010;Fraisse et al, 2011;Uslu et al, 2011;Cornelisse et al, 2012;Sharma et al, 2015), and three had PGI 2 treatment and control groups (Takahashi et al, 2003;Xu et al, 2015;Onan et al, 2016). Based on subgroups of pediatric PH patients, there were seven studies of PPHN (Juni et al, 2006;Wessel et al, 2006;Kolaee et al, 2009;Vargas-Origel et al, 2010;Uslu et al, 2011;Gibbs and Ismail, 2012;Steinhorn et al, 2016), two studies of PPAH (Cornelisse et al, 2012;PAN and KONG, 2016), and six studies of POPH (Takahashi et al, 2003;Peiravian et al, 2007;Fraisse et al, 2011;Sharma et al, 2015;Xu et al, 2015;Onan et al, 2016). A list of pulmonary vasodilator subgroups used in pediatric PH patients is shown in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…PGI 2 analogs are increasingly used for management of pulmonary hypertension in children (21,36) as well as neonates (29,55). Iloprost has been used in extremely preterm infants, primarily for the management of pulmonary hypertension (19,56), although no studies have evaluated its utility for the prevention of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…117,118 Iloprost is appealing because it can be administered via inhalation; however, studies have shown unfavourable haemodynamics and pulmonary congestion. [119][120][121][122][123] Systemic medications such as sildenafil and BQ123 lower pulmonary vascular resistance, but also cause systemic effects such as hypotension. [127][128][129][130][131] Pulmonary hypertension is a significant post-operative complication that can have high mortality.…”
Section: Pulmonary Vasodilatorsmentioning
confidence: 99%